Pemanfaatan Siniar Untuk Pembelajaran Bahasa Indonesia - Priyo Budi Santoso Sinaga; Rahmat Kartolo (Jurnal Komunitas Bahasa, 2025)
The rapid advancement of information technology has fostered the emergence of new media that can be utilized in various fields, including education. Among these, podcasts have gained prominence as dynamic and accessible platforms with great potential for enhancing the learning experience. This study aims to examine the effectiveness and pedagogical value of podcasts as a learning medium in teaching the Indonesian language. A descriptive qualitative method was employed, with data collected through literature review, observation, and documentation of academic sources such as scholarly books and journal articles. The data were analyzed using content analysis to interpret the role of podcasts in educational contexts. The findings indicate that podcasts are not only effective and practical but also contribute significantly to creating interactive learning environments and improving students’ Indonesian language proficiency. Moreover, podcasts offer diverse, flexible content that fosters student engagement and motivation. Thus, integrating podcasts into language instruction represents a relevant and innovative approach to enhancing the quality of Indonesian language education in the digital age.